Knowledge, nutrition and coaching pedagogy: a perspective from female Brazilian Olympic gymnasts - Stewart, Carly; Schiavon, Laurita Marconi [UNESP]; Bellotto, Maria Luisa (Routledge Journals, Taylor & Francis Ltd, 2017)
It is acknowledged that knowledge and knowledge bases are an important part of coach and athlete learning and that the coach - athlete relationship is crucial to knowledge created, shared and used. This said knowledge about nutrition as constructed by elite gymnasts would seem particularly important in a culture long associated with weight control practices and disordered eating. This paper provides an insight into the ways that 10 Brazilian Olympic gymnasts construct ideas pertaining to nutritional knowledge across generational periods (between 1980 and 2004) where significant organisational change in Women's Artistic Gymnastics in Brazil occurred and included the introduction of dieticians. Drawing upon different knowledge types and paying attention to the coaching context, the life histories of 10 Olympic gymnasts were used to open a window on knowledge construction pertaining to nutrition by three generations of gymnasts. The findings draw attention to two main illustrative themes. Firstly, coaches' personal knowledge, whilst perceived as incomplete by gymnasts, reinforced a narrative of weight loss for gymnasts regardless of generation. Secondly, the younger generations of gymnasts perceived that the introduction of dieticians into structured provision enabled them to use better structured knowledge, and with it a sense of increased autonomy and corporeal learning via the construction of tacit embodied knowledge leading to healthier practices. Reflections are given to the role of the coach, dieticians and pedagogical actions, and the continued reshaping of knowledge in elite gymnastics.
Keywords: Nutrition; Knowledge; Tacit; Gymnastics; Coaching; Culture